Efektivitas Pengelolaan Dana Desa Program Bantuan Langsung Tunai (BLT) dalam Peningkatan Kesejahteraan di Desa Lumban Purba - Silaban, Royani; Adam, Adam; Deliana, Marlina (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2024)
Village fund management in the Direct Cash Transfer (BLT) program in Lumban Purba Village is a policy that aims to provide assistance to economically affected poor people, especially after the COVID-19 pandemic. This study aims to evaluate the effectiveness of village fund management in the BLT program in improving welfare in Lumban Purba Village, while also identifying inhibiting factors. The research method used is qualitative with a descriptive approach, involving data collection techniques such as observation, interviews, documentation, and triangulation. Duncam's theory of effectiveness is used with indicators of goal achievement, integration, and adaptation. Research informants include village heads, hamlet heads, village treasurers, as well as BLT recipient and non-recipient communities. The results showed that even though program integration has been effective, the achievement of goals is still not optimal due to errors in aid distribution, and program adaptation has not been effective due to the absence of data revisions during program implementation. Inhibiting factors include the lack of means to convey people's aspirations and data inaccuracies caused by the lack of regular data revisions.